Inner filter effect on amino-functionalized metal-organic framework for the selective detection of tetracycline. (1st November 2022) - Yazhini, Crescentia; Rafi, Jithin; Chakraborty, Paromita; Kapse, Samadhan; Thapa, Ranjit; Neppolian, B.
Abstract: The use of tetracycline (TC) for the treatment of infectious diseases caused by bacteria has been humongous over the past few decades. However, the presence of untreated TC in freshwater leads to antimicrobial resistance. To prevent this concern from damaging the freshwater system, a stable sensor with high selectivity and rapid detection towards TC is desirable. Metal-Organic Frameworks (MOFs) are organic-inorganic hybrid structures with excellent stability, multifunctional ability, and tuneable pore structure that find extensive applications in detection techniques. The structural adaptability, excellent porosity and large surface area of MOFs prove advantageous in terms of adsorption of antibiotics. With this insight, a highly stable Zn-based Luminescent Metal-Organic Framework (LMOF) for the selective detection of tetracycline was developed. It is worth mentioning that, the LMOF-based sensor showed no depreciation in luminescence activity and can be reused more than 10 times. Moreover, a very low detection limit of 0.11 μM and a Stern-Volmer quenching constant (Ksv ) value of 1.16 × 10 4 M −1 indicate its sensitivity precision towards TC detection. A significant inner filter effect of TC was observed in addition to adsorption of TC on the MOF through hydrogen bonding. Further, test strips based on IRMOF-3 showed satisfactory recovery in real-time samples. Thus, the stimuli-responsive sensor reports a simple strategy for excellent sensing performance towards TC. Graphical abstract: Image 1 Highlights: Highly stable sensor for efficient detection of tetracycline is developed. A very low detection limit of 0.1 μM is achieved. A turn-off quenching by inner filter effect mechanism is observed. Portable test strips are produced to facilitate real-time sensing.